MEMBANGUN KARAKTER ANAK DALAM KELUARGA MENURUT EFESUS 4:2 - Meldy Novita Subu Taopan; Ezra Tari (CV. ADIBA AISHA AMIRA, 2024)
The role of parents in forming character is very important, and influences children's character education. Parents in this role also experience difficulties. Researchers want to study two things further: first, what is the role of parents according to Ephesians 4:2 in teaching children's character? Second, how do parents face the challenges of teaching children's character? The purpose of this writing is to increase our understanding of children's character which must be applied in the family according to Ephesians 4:2. The type of research used is the library research method. The approach chosen is qualitative description. By paying attention, educating and accompanying children from an early age, parents can help build their child's character. In Ephesians 4:2 it is an example in building children's character so that parents are role models for their children, for this reason parents should be good examples for their children.